Analysis of Heavy Metal Content of Mercury (Hg) and Cadmium (Cd) in Frozen Tuna (Thunnus sp.) - Iftachul Farida; Anis Khairunnisa; Gusti Ngurah Putu Paksi Kencana (JFMR (Journal of Fisheries and Marine Research), 2024)
Tuna fish is one of the fishery resources that has high potential. The fish is very active and vulnerable to chemical contamination because marine waters include areas that have a lot of contact with humans such as accretion, fish processing industries, and metal smelting. This study aims to: (1) analyze the content mercury and cadmium in frozen tuna; (2) analyze the effect of fish sample weight on Hg and Cd content. Destructive principle method with Atomic Absorption Spectrophotometer (AAS) used for analyzing the Hg and Cd content. Heavy metal analysis used 5 samples of frozen tuna fish. The samples were taken from a Tuna fish freezing company from the Denpasar area, Bali. Linear regression analysis was used to determine the sample weight effect on heavy metal content in tuna fish. The heavy metal test results showed that all samples contained less than 1.0 ppm of Hg and less than 0.5 ppm of Cd. It shows that heavy metal which contains in all the samples still under the threshold by SNI 7387:2009. Data analysis showed that there was no significant effect of sample weight on Hg content (p>0.05), while weight of sample had a significant effect on Cd metal (p<0.05).